Sharia Pawn Mechanism (Rahn) on BMT Mawaddah Palengaan Branch - Bahri, Mat; Ernawati, Ernawati; Agustin , Dwi Novita (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
cabang Palengaan in running a sharia pawnshop business (rahn). By using the descriptive method with the approach. The findings of this study are based on the Sharia Pawn (Rahn) mechanism in Baitul Maal Wa Tamwil BMT Mawaddah cabang Palengaan, First, the pawn contracts used are rahn and ijarah contracts. Second, the customer disbursement process will be subject to administrative and ujrah fees. Third, there is a process of determining the loan ceiling that will be given to customers. Fourth, the repayment process applies 2 ways, namely, the installment model and repayment at the 3 month maturity date. Fifth, if there are customers who are unable to pay off loans according to maturity, there are 2 ways of handling them, namely, taking a direct approach to provide settlement solutions and the auction process. Academic recommendations from this research, there is a need for further research with a wider unit of analysis.